ANALYSIS OF THE FACTORS THAT AFFECT THE COMPANY'S ACCOUNTING CONSERVATISM - Wulan Wahyuni Rossa Putri; Nilda Tartilla; M. Nofal Pamungkas (The Accounting Journal of Binaniaga, 2020)
Accounting conservatism is a precautionary principle in financial reporting. In this principle, it slows down the recognition of revenue and accelerates the recognition of costs so as to result in lower profits and assets, as well as high costs and debt. This study aims to determine the factors that affect accounting conservatism in the Property Real Estate and Buliding Construction sector manufacturing companies listed on the IDX.The data source used in this research is secondary data. Data is sourced from audited annual reports obtained from the IDX official website, namely www.idx.co.id. The population of this research is manufacturing companies listed on the Indonesia Stock Exchange, with research samples in the Property Real Estate and Buliding Construction sector in the 2013-2017 period. The samples were determined using purposive sampling method. The method of analysis used in this research is multiple regression with the SPSS version 25 program and hypothesis testing is done using multiple linear regression method.The results of this study indicate that leverage has no effect on accounting conservatism with a significance value of 0.554. Financial distress has no effect on accounting conservatism with a value of 0.852. Meanwhile, capital intensity has an effect on accounting conservatism with a significance value of 0.000. As well as Leverage, Financial Distress, and Capital Intensity simultaneously affect accounting conservatism.